THE IMPORTANCE OF MANNA COUNTRY IN FOREIGN POLITICS OF THE URARTU STATE - ÖZMEN, Seher Selin (SSD Journal, 2022)
The Manna State was established in the south of Lake Urmia in the 9th century BC. The name of this state is mentioned in Urartian and Assyrian cuneiform sources from the 1st millennium BC. The region where the land of Manna located is particularly important as it is on trade routes when a great drought and thus a wave of migration from Central Asia began during the Iron Age. Urmia Lake Basin, which has attracted the attention of the Urartian Kingdom from the early period, is one of the regions that could not be dominated and therefore almost all Urartian kings organized expeditions. The attempt to subdue Manna increased during the reign of the Urartian King Menua and the Assyrian threat was faced during the intense campaigns during the reign of Menua’s successor, Argišti I. During the Sarduri II period, expeditions continued and tribute was taken from the Manna principalities. Manna King Iranzu, who was an Assyrian vassal, took advantage of Assyrians’ successful war against Urartu, followed a policy of centralization and created a principality system dependent on the central authority in the country. Although Manna became a powerful state around the Urmia Lake Basin during Iranzu’s reign, some rulers and princes who did not like Iranzu’s centralization policy gave Urartu the opportunity to interfere in Manna’s internal affairs. Urartian King Rusa I used the internal political crisis among the Mannas for his own purposes, provoked some principalities against the central authority, and a pro-Urartian group emerged in the country. Thus, the Lake Urmia Basin became the subject of an intense struggle for dominance between the Urartu and Assyrian States during the reign of Rusa I. With the Assyrian King Sargon II, the pressure of the Urartians in the region decreased. After the defeat of Urartian Kingdom by Sargon II, the balance of power in the region changed, and Manna was not mentioned in Urartian written sources after that. In this study, the importance of the Manna State, which has an important place in the history of Azerbaijan, in terms of the foreign policy of the Urartian State is discussed.